2021
DOI: 10.1007/s40199-020-00386-1
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan-induced immune hemolytic anemia in 17 years old man. A case report

Abstract: Hemolytic anemia is a very important immune-mediated reaction, which its late diagnosis can be fatal. Medications along with other causes can induce hemolytic anemia. Drug induced immune hemolytic anemia (DIIHA) is caused by the development of autoantibodies. Accordingly, DIIHA is rare and there is not enough data for its prevalence. Number of drugs that can cause DIIHA have increased in recent decades. A 17-year-old man who had congenital single ventricle heart (CHB) and pulmonary artery hypertension (PAH) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In China, DIIHA has not yet been included in the medication risk monitoring system. It is now clear that there are nearly 140 drugs that can cause DIIHA through immune complex mechanisms (ie, drug-induced antibodies) [5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]38] , but DIIHA has not been included in the list of side effects of these drugs, and there is a lack of DIIHA vigilance, the vast majority of DIIHA may be missed, misdiagnosed, delayed in diagnosis, or given improper intervention, which increases the risk of patients' administration. Incorporating DIIHA into the medication risk monitoring system and improving the awareness and vigilance of DIIHA will help avoid the serious consequences of DIIHA on patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, DIIHA has not yet been included in the medication risk monitoring system. It is now clear that there are nearly 140 drugs that can cause DIIHA through immune complex mechanisms (ie, drug-induced antibodies) [5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]38] , but DIIHA has not been included in the list of side effects of these drugs, and there is a lack of DIIHA vigilance, the vast majority of DIIHA may be missed, misdiagnosed, delayed in diagnosis, or given improper intervention, which increases the risk of patients' administration. Incorporating DIIHA into the medication risk monitoring system and improving the awareness and vigilance of DIIHA will help avoid the serious consequences of DIIHA on patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NIPA mechanism can only cause a positive result of the direct antiglobulin test (DAT) and slow, di cult to observe slight hemolysis [6][7][8] . It has been reported that nearly 140 kinds of drugs can cause DIIHA through drug-induced antibodies, and there are 10 kinds of drugs with NIPA effect [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 140 drugs are associated with drug-induced immune hemolytic anemia (DIIHA) (1)(2)(3)(4)(5)(6)(7)(8)(9). The pathogenic mechanism of DIIHA involves the damage of red blood cells (RBCs) by drug-induced (drug-dependent and -independent) antibodies or non-immune protein adsorption (NIPA) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced immune hemolytic anemia (DIIHA) is a rare disease resulting from immune damage to red blood cells (RBCs) caused by drug-induced antibodies or non-immunologic protein adsorption (NIPA) (1)(2)(3)(4), and nearly 140 drugs have been reported to cause DIIHA via drug-induced antibodies, and approximately 10 via NIPA (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Cefotaxime (CTX) is a thirdgeneration cephalosporin, which is a b-lactam broad-spectrum antibiotic.…”
Section: Introductionmentioning
confidence: 99%